The evaluation of the effectiveness of marketing mix (4 p’s) implementation activities towards performances of Perdana Resort, Pantai Cahaya Bulan, Kota Bharu from the guests’ perspectives / Amira Mohd Azhar - Mohd Azhar, Amira (2014)
The researcher studies about the evaluation of the effectiveness of marketing mix (4 P’s) implementation activities towards performances of Perdana Resort, PCB Beach from the guests’ perspectives. There are four (4) factors in the study which are products, price, promotion and place in order to see the affecting factors that influence the performances of Perdana Resort, PCB Beach. The objective of this study is to determine the effectiveness of marketing mix (4 P’s) implementation activities towards performances of Perdana Resort, PCB Beach from the guests’ perspectives. Then, this study can give suggestions and recommendations to Perdana Resort, PCB Beach on how to improve the implementation of 4 P’s. Data were gathered from the questionnaires which were distributed to 100 respondents that visit Perdana Resort, PCB Beach. The data were analyzed using SPSS through the reliability analysis, frequencies analysis, cross tabulation, correlation coefficient analysis, mean analysis and regression. From the result, the researcher found that products, price, promotion and place have a positive significant relationship with the performances of Perdana Resort, PCB Beach. From the findings, it shows that product is the most effective in implementing its products element of marketing mix which is (mean=3.6383) while promotion is not effective in implementing its promotion element of marketing mix which is (mean=3.2571). Some conclusions are provided in this research and the researcher also stated several recommendations based on the results. It is a great pleasure if Perdana Resort, PCB Beach is willing to evaluate the suggestions from the respondents and the researcher and propose to their resort management